Middle Devonian chitinozoan assemblages of northwestern Argentina and southern Bolivia: New biostratigraphic and palaeogeographical insights - Camina, Sonia Clara (2025)
Chitinozoans from the Middle Devonian Los Monos Formation in the Tarija Basin (southern Bolivia and northwestern Argentina) have been analysed from the Tacobo TCB X-1001 (TCB-1001) and Ramos R-1011 (R-1011) boreholes. While the chitinozoan assemblages from the TCB-1001 borehole have been previously published, this contribution presents a comprehensive new analysis of the R-1011 material and integrates it into a refined biostratigraphic and palaeogeographical framework. Thirty-eight cutting samples were processed, yielding specimens in eighteen samples that allowed for taxonomic classification. A total of 11 genera and 40 species of chitinozoans were identified from both boreholes. Twenty species were identified in the R-1011 borehole, including the newly described species Lagenochitina postpirum n. sp. and Ramochitina durandi n. sp. Based on an integrated biostratigraphic analysis, three local chitinozoan biozones are proposed: the late Eifelian-early Givetian Ramochitina candelariaensis–stiphrospinata Biozone, the early Givetian Ancyrochitina flexuosa–Ramochitina ramosi Biozone, and the middle Givetian Ancyrochitina cornigera–Ramochitina autasmirimense Biozone. A palaeogeographical analysis using similarity indices indicates that there were no geographic barriers within the Tarija Basin and suggests interconnections among all Western Gondwana basins. However, the results for other palaeocontinents suggest that the Western Gondwana chitinozoan fauna did not mix with other faunas worldwide.